2010
DOI: 10.1007/s11427-010-0026-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of MC1R gene in buffalo coat color

Abstract: Melanocortin-1 receptor (MC1R) plays a major role in pigmentation in many species. To investigate if the MC1R gene is associated with coat color in water buffalo, the coding region of MC1R gene of 216 buffalo samples was sequenced, which included 49 black river buffalo (Murrah and Nili-Ravi), 136 swamp buffalo (Dehong, Diandongnan, Dechang, Guizhou, and Xilin) with white and gray body, and 31 hybrid offspring of river buffalo Nili-Ravi (or Murrah) and swamp buffalo. Among the three variation sites found, SNP68… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 30 publications
(32 reference statements)
3
24
1
Order By: Relevance
“…Importantly, these residues are selectively important for the constitutive activity of E92K as the agonist-induced activation by αMSH is not affected by Ala-substitution (Figure 7, insets). Interestingly, a dominant G104S mutation at the equivalent position to G102 has recently been identified in MC1R of the water buffalo [37]. This mutation was perfectly associated with a black coat color and although not pharmacologically characterized it was estimated to be of functional importance by in silico analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these residues are selectively important for the constitutive activity of E92K as the agonist-induced activation by αMSH is not affected by Ala-substitution (Figure 7, insets). Interestingly, a dominant G104S mutation at the equivalent position to G102 has recently been identified in MC1R of the water buffalo [37]. This mutation was perfectly associated with a black coat color and although not pharmacologically characterized it was estimated to be of functional importance by in silico analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analysis of dam–calf data indicated dominance of the white colour over black in swamp buffalo (Rife & Buranamanas ). Miao et al () identified two missense mutations in the river buffalo MC1R gene, but these did not explain the difference between white and dark grey swamp buffalo. White‐spotted buffalo (Fig.…”
Section: Introductionmentioning
confidence: 98%
“…In addition to colour inheritance in cattle [18], information is also available on sheep [19], goat [20] and buffalo [21]. However, nothing is known about colour inheritance in Cervids.…”
Section: Introductionmentioning
confidence: 99%